Outcome of Coronary Artery Diseases in 12 weeks Treatment Tenure - Sufian, Mir; Zahid, Abu; Islam, Hasanul; Kabir, Ahsanul; Siddiqui, Mahbub Alam; Hossain, Muktar; Kadir, A.N.M. Monowarul; Sultana, Israt (Cardiology and Cardiovascular Medicine, 2023)
Backgraound: Prediction of the proximal right coronary artery lesion in the setting of acute inferior myocardial infarction is very crucial for the reduction of significant morbidity and mortality. Objective: The objective of the study was to determine the validity of right ventricular free wall strain detected by spickle-tacking echocardiography for identifying proximal right coronary artery lesion in acute inferior myocardial infraction. Methodology: This cross sectional observational study was carried out at the Department of Cardiology and the Department of Echocardiography of National Heart Foundation Hospital and Research Institute from March 2020 to February 2021. 80 patients with acute inferior MI were included in this study. Echocardiographic examination was done with the measurement of conventional parameters and strain analysis. Patients with RCA occluded proximal to right ventricular branch were assigned to group I and patients with RCA occluded distal to right ventricular branch were assigned to group II. Correlation was done with the echocardiographic and angiographic parameters. Results: RV-FW strain was lower in group I patients compared to group II (-12.21±4.22 % vs -18.16±2.93 %). Based on ROC curves average RV-FW at a cut off value of ≥ -15.8 % predicted proximal RCA lesion with 83.0% sensitivity and 75.8% specificity which was much reliable than the sensitivity and specificity of other conventional parameters like FAC (44.7% and 39.4%), TAPSE (48.9% and 39.4%) and TDI-TV Sm (44.7% and 30.3%). Conclusion: RV-FW strain at a cutoff value of ≥ -15.8 % is an independent predictor of the proximal RCA lesion in patients with acute inferior MI.